The physical health of young people experiencing first-episode psychosis: Mental health consumers’ experiences - Chee, G.; Wynaden, Dianne; Heslop, Karen (Wiley-Blackwell Publishing Asia, 2018)
© 2018 Australian College of Mental Health Nurses Inc. Young people experiencing first-episode psychosis taking antipsychotic medications often develop comorbidities such as obesity and cardiometabolic abnormalities at an earlier age than young people in the general population. Therefore, it is important to explore the healthcare needs and experiences of this group of consumers. This paper reports research conducted to obtain an informed understanding of young people's health literacy, physical healthcare needs, and interest and knowledge about their physical health. Grounded theory methodology was used to guide the research. Semistructured interviews were conducted with 24 young consumers aged between 18 and 35 years who were case managed by one metropolitan community mental health service. The results describe the journey of young people from the time of diagnosis, to when they developed an awareness of the need to improve their physical health and the impact of physical health issues on their overall health and well-being. Six categories emerged from the data: (i) initial responses when diagnosed with first-episode psychosis; (ii) focus of care on treating first-episode psychosis; (iii) lack of education on antipsychotic medications; (iv) adverse effects from taking antipsychotic medication; (v) increased awareness of the need for good physical health; and 6) importance of social support in the community. The findings highlight the importance for health professionals improving young people's health literacy and addressing physical health and well-being as part of first-episode psychosis programmes. Young people require improved health education on the importance of maintaining healthy lifestyle in relation to their overall health and well-being.